2022
DOI: 10.3389/fcimb.2022.947382
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota: A Novel Player in Autoimmune Hepatitis

Abstract: Autoimmune hepatitis (AIH) is a chronic immune-mediated liver disease distributed globally in all ethnicities with increasing prevalence. If left untreated, the disease will lead to cirrhosis, liver failure, or death. The intestinal microbiota is a complex ecosystem located in the human intestine, which extensively affects the human physiological and pathological processes. With more and more in-depth understandings of intestinal microbiota, a substantial body of studies have verified that the intestinal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 110 publications
(265 reference statements)
0
34
0
Order By: Relevance
“…This complex then enters the liver through the circulation of the portal vein, triggering a cascade of intracellular signals in liver through TLR4, which eventually leads to exacerbated liver fibrosis ( Seki et al., 2007 ), cirrhosis ( Milosevic et al., 2019 ; Wang et al., 2022 ) and even liver cancer ( Meng et al., 2018 ). This interaction effect between the gut microbiota and the liver mediated by the LPS-TLR4 signaling pathway is called the gut-liver axis ( Seki et al., 2007 ; Chassaing et al., 2014 ; Cheng et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This complex then enters the liver through the circulation of the portal vein, triggering a cascade of intracellular signals in liver through TLR4, which eventually leads to exacerbated liver fibrosis ( Seki et al., 2007 ), cirrhosis ( Milosevic et al., 2019 ; Wang et al., 2022 ) and even liver cancer ( Meng et al., 2018 ). This interaction effect between the gut microbiota and the liver mediated by the LPS-TLR4 signaling pathway is called the gut-liver axis ( Seki et al., 2007 ; Chassaing et al., 2014 ; Cheng et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that FMT could modulate imbalance of T follicular regulatory (TFR) and T follicular helper (TH) cells and gut microbiota composition by immune pathways in vivo. Furthermore, metabolite pathways (e.g., short-chain fatty acid, amino acid, and bile acid) and receptor pathways (e.g., Toll-like receptor 4 (TLR4), and G protein-coupled receptors (GRP41/GPR43, GPR109a) in the intestine, while nucleotide-binding and oligomerization domain NOD-like receptors (NLRs), TLR4, TLR9, and GPBAR1 in liver) were found as the influential mechanisms of altered gut microbiota in AIH [ 79 ]. The above-mentioned evidence verified the underlying therapeutic value of FMT for AIH.…”
Section: Fecal Microbiota Transplantation (Fmt) In the Treatment Of L...mentioning
confidence: 99%
“…Molecular mimicry may also be a mechanism that accelerates or sustains autoimmune hepatitis [ 44 , 73 , 125 ] (Table 2 ). The release of neo-antigens from damaged liver tissue [ 126 , 127 ] or the translocation of bacterial products from a permeable intestine [ 44 , 47 , 128 135 ] could promote molecular mimicry and affect the severity and course of autoimmune hepatitis. Furthermore, molecular mimicry could contribute to the ongoing inflammatory process by expanding the number of targeted epitopes (epitope spread) [ 136 139 ] and the population of memory CD4 + and CD8 + T cells (bystander activation) [ 140 , 141 ].…”
Section: Molecular Mimicry and Environmental Pathogensmentioning
confidence: 99%
“…Diet [ 25 , 134 ], supplements [ 24 ], antibiotics [ 23 ], alcohol [ 23 ], pollutants [ 23 ], and toxins [ 26 ] have been associated with the risk of autoimmune hepatitis, and this risk may reflect changes in the intestinal microbiome induced by these diverse environmental factors [ 25 , 26 , 42 47 ] (Table 2 ). Findings in experimental models of autoimmune hepatitis [ 129 , 184 ] and other autoimmune diseases [ 185 188 ] have supported this premise, albeit there are many other factors outside of molecular mimicry that may be contributory [ 45 47 , 135 , 189 ].…”
Section: Molecular Mimicry and Gut-derived Microbial Productsmentioning
confidence: 99%
See 1 more Smart Citation